Is adhesive bonding with high and low viscosity cements able to revert the negative effect of machining on the fatigue behavior of lithium disilicate glass-ceramic? - May, Michele Mirian (2024)
The aim of this study was to evaluate the fatigue behavior of adhesively cemented machined and polished lithium disilicate discs and compare the influence of the resin cement viscosity used to bond the ceramics to dentin analog substrate. Disc-shaped specimens (n = 15, Ø = 12 mm; thickness = 1.3 mm) of CAD-CAM lithium disilicate (IPS e.max CAD, Ivoclar Vivadent) were prepared and divided according to processing and surface finishing (machining (M) – CEREC inLab; and polishing (P) – control) and cement viscosity (high (H) and low (L)). The specimens were treated with self-etching primer and adhesively cemented (Variolink N Base + High or Low viscosity catalyst, Ivoclar Vivadent) to dentin analog discs (Ø = 12 mm; thickness = 2.2 mm). The cemented assemblies were subjected to fatigue testing using a step-stress approach (500−1500 N; step-size of 100 N; 10,000 cycles per step; 20 Hz). Weibull statistics were conducted on fatigue data (95 % CI). Fractographic and topographic analyzes were also performed on a scanning electron microscope (SEM). Considering the same viscosity, machined groups presented statistically lower characteristic fatigue failure load (N) (FFL0 MH 1192 [1111–1278]; ML 1105 [1077–1134]) than their polished controls (FFL0 PH 1350 [1279–1424]; PL 1333 [1276–1392]). No differences were found between cement viscosities, regardless of surface characteristic. It is well known that CAD-CAM machining impairs mechanical performance of lithium disilicate glass-ceramics. Adhesive cementation was not able to revert this negative impact, regardless of cement viscosity. Cement viscosity did not affect the fatigue results.